2021
DOI: 10.3390/universe7020025
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Uncertainties in Low-Metallicity AGB Stars: The Impact on Stellar Structure and Nucleosynthesis

Abstract: The slow neutron-capture process (s-process) efficiency in low-mass AGB stars (1.5 < M/M⊙ < 3) critically depends on how mixing processes in stellar interiors are handled, which is still affected by considerable uncertainties. In this work, we compute the evolution and nucleosynthesis of low-mass AGB stars at low metallicities using the MESA stellar evolution code. The combined data set includes models with initial masses Mini/M⊙=2 and 3 for initial metallicities Z=0.001 and 0.002. The nucleosynthesis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Nonetheless, we expect a non-trivial mass-metallicity dependence of the mixing triggered by magnetic buoyancy (as for other type of mixing, see e.g. Joyce & Chaboyer 2018;Battino et al 2021). In particular, the toroidal field strength is determined by the differential rotation profile established in the He-intershell and which amplifies the magnetic field via dynamo action (see Section 4).…”
Section: Stellar Modelsmentioning
confidence: 95%
“…Nonetheless, we expect a non-trivial mass-metallicity dependence of the mixing triggered by magnetic buoyancy (as for other type of mixing, see e.g. Joyce & Chaboyer 2018;Battino et al 2021). In particular, the toroidal field strength is determined by the differential rotation profile established in the He-intershell and which amplifies the magnetic field via dynamo action (see Section 4).…”
Section: Stellar Modelsmentioning
confidence: 95%
“…Vescovi et al (2020) found that most of the heavy-element isotope ratios measured in presolar SiC grains from AGB stars are consistently explained by stellar AGB models computed with a unique choice for the toroidal field strength and the initial buoyant velocity, namely B ϕ = 5×10 4 G and u p = 5×10 −5 cm s −1 . Nonetheless, we expect a nontrivial mass-metallicity dependence of the mixing triggered by magnetic buoyancy (as for other type of mixing; see, e.g., Joyce & Chaboyer 2018;Battino et al 2021). In particular, the toroidal field strength is determined by the differential rotation profile established in the He-intershell that amplifies the magnetic field through dynamo action (see Sect.…”
Section: Stellar Modelsmentioning
confidence: 95%
“…The formation of an extended 13 C pocket induced by mixing processes can increase Ce production (e.g. Battino et al 2021) and may explain its overabundance in the young open clusters, as pointed out by Maiorca et al (2011).…”
Section: Discussionmentioning
confidence: 96%